Pentingnya Masail Fiqhiyah dalam Kehidupan Dunia Modern - Nursaman (Tarbawi : Jurnal Studi Pendidikan Islami, 2022)
Islamic law regulates various life issues in detail. At the time it was revealed there was not a single human life that was not regulated. There are things that are regulated in a standard way and cannot change forever, namely regarding worship of Allah, but there are things that are regulated dynamically following developments in era, place and time, namely Muamalah, human relationships with other humans and the universe. Masail Fiqhiyah is known as a scientific discipline regarding the dynamics of Islamic law. Research on the urgency of Masail fiqhiyah in the modern world is normative research on how Islamic jurisprudence adapts to increasingly complex developments. The problem raised is: What is meant by Masail Fiqhiyah in Islamic terminology? How does Islamic Law solve contemporary problems in the modern world? The results of the research show that academically, Masail Fiqhiyah is a discipline of Fiqh related to legal issues in human life that is contemporary or does not yet have legal texts from various schools of thought. The solution to this matter is by using the Ijtihad method, not using Ijma' or agreement as existing in Islamic Fiqh.